LEXICAL AND GRAMMAR COHESION IN THE COLLECTION OF "MUSEUM PENGHANCUR DOKUMEN" POETRY BY AFRIZAL MALNA - Marlina Agkris Tambunan (BASIS (Bahasa dan Sastra Inggris), 2019)
The purpose of this study is to describe the elements of lexical cohesion and grammatical cohesion elements in the poem discourse "Museum of Destruction of Documents" by Afrizal Malna. This research uses descriptive qualitative method by using library, reading, and note taking techniques. Data analysis was performed by data reduction, data presentation, then described and verified. Based on the research findings, it was concluded that the grammatical cohesion used in the collection of poetry "Museum Destroyer Documents" by Afrizal Malna found as many as 313 markers which include; 1) referencing 168 markers; 2) absorption of 2 markers; and 3) assembling 143 markers. Furthermore, the use of lexical cohesion used in the discourse on the poem "Document Shredder" by Afrizal Malna was found as many as 93 markers which included; 1) repetition of 39 markers; 2) synonym 11 markers; 3) antonimi 29 markers; 4) collocation of 9 markers; and 5) equivalence of 5 markers. When combined, the total usage of both is 406 markers.